Neighbourhood characteristics and confidence in the police in the context of South Korea - Kwak, Hyounggon (Policing and society, 2019)
This study examines the generalisability of research on neighbourhood influences on confidence in the police to the context of South Korea. In addition, we propose and test a theoretical model in which neighbourhood context influences confidence in the police indirectly via collective efficacy. We estimate multilevel models using the 2008 Korean Crime Victimization Survey. Neighbourhood disorder, residential stability, and collective efficacy affected citizens’ confidence in the police. The effects of disorder and residential stability on perceptions of the police were mediated by collective efficacy. We confirmed that several factors that have been shown to influence confidence in the police in the West are also important predictors in South Korea. Police need to be more concerned about issues such as disorder, social cohesion, and moral consensus, because when these values and structures are under threat, residents are more likely to have lower levels of confidence in the police.